Experimental and Numerical Simulation of Desorption and Diffusion Process of the Adsorbed Gas in Coal Rock under Isothermal Conditions - Xiaohu Zhang; Hui Li; Chunguang Wang; Zhifeng Zhao; Lifeng Li; Xiao Wang (Geofluids)
Investigation of desorption of diffusion migration of native adsorbed gas in coal under the action of temperature has always been one of the important directions of coal mine safety research. Five coal samples from the Sichuan Furong mining area are studied under the different isothermal conditions (35°C, 30°C, 24.5°C, 36.2°C, and 40°C) by means of laboratory tests; the desorption, diffusion, and migration processes of adsorbed gas were studied; the escaped gas volume in the process of diffusion, the escaped gas pressure, and the change of the concentration of the gas component content are summarized; and the emitted gas volume curve will be eventually found to be constant under the isothermal process. In addition, the escaped gas concentration showed a trend of increasing first and then decreasing. Based on the CT scan slice of coal samples, a network model of coal fracture based on the Tyson polygon contraction method is established in this paper, and LS-DYNA software is used to analyze the transient diffusion behavior of methane under three isothermal conditions (24.5°C, 30°C, and 42°C), and the experimental results are verified.